Associations of Prenatal First Trimester Essential and Nonessential Metal Mixtures with Body Size and Adiposity in Childhood. Issue 1 (17th October 2022) - Smith, Anna R.; Lin, Pi-I D.; Rifas-Shiman, Sheryl L.; Wright, Robert O.; Coull, Brent; Hivert, Marie-France; Hubbard, Alan; Oken, Emily; Cardenas, Andres
Abstract : Background: Prenatal nonessential metals may contribute to postnatal adiposity, whereas essential metals may have metabolic benefits. We evaluated joint and individual associations between prenatal metals and childhood adiposity. Methods: We measured concentrations of six nonessential (arsenic, barium, cadmium, cesium, lead, and mercury) and four essential (magnesium, manganese, selenium, and zinc) metals in first trimester maternal blood from a prebirth cohort. We collected anthropometric measures in early childhood, mid-childhood, and early adolescence including subscapular+tricep skinfold thickness (mm) (N = 715–859), waist circumference (cm) (N = 717–882), and body mass index (BMI) (z-score) (N = 716–875). We measured adiposity in mid-childhood and early adolescence using bone densitometry total- and trunk- fat mass index (kg/m 2 ) (N = 511–599). We estimated associations using adjusted quantile g-computation and linear regression. Results: The nonessential metal mixture was associated with higher total (β = 0.07, 95% CI = 0.01, 0.12) and trunk fat mass index (β = 0.12, CI = 0.02, 0.22), waist circumference (β = 0.01, CI = 0.00, 0.01), and BMI (β = 0.24, CI = 0.07, 0.41) in mid-childhood, and total fat mass index (β = 0.07, CI = 0.01, 0.14), and BMI (β = 0.19, CI = 0.02, 0.37) in early adolescence. The essential metal mixture was associated with lower early adolescence total-(β = –0.11, CI = –0.17, –0.04) and trunk- fat mass index (β = –0.13, CI = –0.21, –0.05), subscapular+tricep skinfold thickness (β = –0.02, CI = –0.03, –0.00), waist circumference (β = –0.003, CI = –0.01, –0.00), and BMI (β = –0.16, CI = –0.28, –0.04). Cadmium and cesium were individually associated with childhood adiposity at different timepoints. Conclusions: Prenatal first-trimester essential metals were associated with lower childhood adiposity, whereas nonessential metals were associated with higher adiposity into adolescence.